Are men universally more dismissing than women? Gender differences in romantic attachment across 62 cultural regions - Schmitt, David P. (2003)
Gender differences in the dismissing form of adult romantic attachment were investigated as part of the International Sexuality Description Project a survey study of 17,804 people from 62 cultural regions. Contrary to research findings previously reported in Western cultures, we found that men were not significantly more dismissing than women across all cultural regions. Gender differences in dismissing romantic attachment were evident in most cultures, but were typically only small to moderate in magnitude. Looking across cultures, the degree of gender differentiation in dismissing romantic attachment was predictably associated with sociocultural indicators. Generally, these associations supported evolutionary theories of romantic attachment, with smaller gender differences evident in cultures with high–stress and high–fertility reproductive environments. Social role theories of human sexuality received less support in that more progressive sex–role ideologies and national gender equity indexes were not cross–culturally linked as expected to smaller gender differences in dismissing romantic attachment.